Regional Aspects of Banks Activity: Comparative Analysis of International Operation of Russian and Kazakh Banks - Mingaleva, Zhanna; Baurzhan, Israilov; Assel, Jumasseitova (International Journal of Economics and Financial Issues, 2016)
The tendencies of the recent several years include strengthening and sharpening of a number of negative tendencies in the financial and credit area. First of all, this is the transition of inflation from one country to another, increase in political and economic risks, transfer of crises and financial shocks from parent banks to foreign subsidiaries, decrease in the efficiency of the activity of primary banks in a number of countries because of strengthening of non-commercial goals in the activity of banks, etc. Herewith, the impact of regional peculiarities of the activity and risks related to them grow. Based on the application of the method of comparative analysis, regional peculiarities of the activity of Russia and Kazakh banks were researched. The research of foreign regional peculiarities in the activity of banks accentuates on Eastern and Central Europe and CIS countries. According to the results of the research, it has been revealed that international operation of the largest Russian banks is actively developing. However, it is seriously influenced by regional specificity in the activity of banks branches. International operation of national banks of the Republic of Kazakhstan is considerably weaker. However, the representation of foreign banks branches on the financial and banking market of Kazakhstan is considerably greater than in Russia. Keywords: Regional Peculiarities of the Banking Activity; Efficiency of Banks Branches Activity. JEL Classifications: G21, E52, G01.